Properties of furfurylated wood (Pinus pinaster) - Esteves, B. (2011)
Sapwood samples of Pinus pinaster wood were treated with a 70% furfuryl alcohol mixture.Weight percent gain (WPG), equilibrium moisture content, dimensional stability, MOE, bending strength, hardness, density and durability were determined. WPG was on average 38%. Equilibrium moisture content decreased more than 40%. Dimensional stability increased reaching an ASE of 45%.MOE was little affected by the treatment but bending strength increased by about 6%. Hardness increased by about 50%, and density by 37%. Mass loss due to Postia placenta and Coniophora puteana decreased by 96% and 86%, respectively. Furfurylation of Pinus pinaster wood shows an interesting potential to improve the wood quality for solid timber products.